The Contribution of Teachers’ Social and Personality Competence to the Development of a Conducive School Climate - Aminah, Siti; Zebua, Syukurman; Oktari, Rici (Thawalib: Jurnal Kependidikan Islam, 2025)
Teachers' competencies, particularly social and personality competence, play a vital role in shaping a conducive school climate. However, research that examines explicitly their influence within local contexts remains limited. This study aims to determine the extent to which teachers’ social and personality competence affects the development of a conducive school climate at Senior High School 7 Tanjung Jabung Timur, using a quantitative approach. Employing a correlational research design with 183 respondents, data were analyzed using SPSS 26 through validity and reliability tests, classical assumption testing, and multiple linear regression analysis. The findings reveal that teachers’ social competence contributes 7.1% to the formation of a conducive school climate. Meanwhile, personality competence accounts for 12.2% of the variance. Simultaneously, both competencies significantly contribute to the school climate, with a combined contribution of 12.4%. These results suggest that integrating both competencies is essential in fostering a positive school environment. Conclusion: Teachers’ personality competence plays a significant role in creating a conducive school climate, while social competence shows a lesser, statistically insignificant effect, although both levels of competence remain relatively low.